1977
DOI: 10.1111/j.1755-3768.1977.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Function of Keratoprostheses

Abstract: The optical function of acrylic cylinders used in keratoprostheses is demonstrated by using a water-filled minicamera as a model of the aphakic human eye. Lengths and diameters of the optical cylinders are important factors influencing the visual fields. The dimensions to be chosen, depends on the thickness of the cornea and the supporting tissues. The most suitable combination of visual field, magnification and diameter of the retinal image field is obtained with optical cylinders with a concave posterior sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…In eyes with Type I KPros we found about 50° in the temporal direction, compared with the 44° computed, and in Type II, about 40° temporally. These results are also consistent with the 70° diameter measured by Sokol4 for a similarly-dimensioned prosthetic of 4.5 mm length and 3.1 mm diameter, and with the about 100° computed by Rol et al5 for a 3 mm diameter and 3 mm length. While these are very wide fields, it is obvious that in a situation where a patient has one normal eye and the other suffers from severe corneal damage, expanding the visual field is not a good reason for implanting KPro in the damaged eye.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In eyes with Type I KPros we found about 50° in the temporal direction, compared with the 44° computed, and in Type II, about 40° temporally. These results are also consistent with the 70° diameter measured by Sokol4 for a similarly-dimensioned prosthetic of 4.5 mm length and 3.1 mm diameter, and with the about 100° computed by Rol et al5 for a 3 mm diameter and 3 mm length. While these are very wide fields, it is obvious that in a situation where a patient has one normal eye and the other suffers from severe corneal damage, expanding the visual field is not a good reason for implanting KPro in the damaged eye.…”
Section: Discussionsupporting
confidence: 91%
“…The reflected light would result in diffusion circles or circular stripes which can cause a decrease in visual acuity and contraction of the visual field 18. Sokol et al4 painted the side of the cylinders black, resulting in improved image sharpness and contrast, particularly in the periphery. We were able to illustrate a similar phenomenon in the KPro using the computer simulation, assuming that the inner surface of the optical cylinder behaves as a perfect polished mirror.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual fields of our patients were not recorded. However, studies by Sokol et al (1977) have shown a field of about 35 degrees through a 6 mm long optical cylinder, a finding which seemed to correspond well with the general visual performance of our patients. Three eyes with a certain preoperative light perception became completely amaurotic during follow-up.…”
Section: €Toupsupporting
confidence: 79%
“…14 KPro optical cylinder on computer simulations, assuming the inner surface of the cylinder acts like a mirror. 6,15 However, they also suggested that the contribution to total glare from light reflected from the wall of the cylinder was minimal. As the OOKP optical cylinder has a longer tubular wall, the effect of glare in an OOKP eye may be greater than that with the Boston KPro.…”
Section: Discussionmentioning
confidence: 99%